Association between carotid diameter and the advanced glycation end product N-epsilon-carboxymethyllysine (CML) - Baumann, Marcus; Richart, Tom; Sollinger, Daniel; Pelisek, Jaroslav; Roos, Marcel; Kouznetsova, Tatiana; Eckstein, Hans-Henning; Heemann, Uwe; Staessen, Jan A (Cardiovascular diabetology, 2009)
Nepsilon-carboxymethyllysine (CML) is the major non-cross linking advanced glycation end product (AGE). CML is elevated in diabetic patients and apparent in atherosclerotic lesions. AGEs are associated with hypertension and arterial stiffness potentially by qualitative changes of elastic fibers. We investigated whether CML affects carotid and aortic properties in normoglycemic subjects. Hundred-two subjects (age 48.2+/-11.3 years) of the FLEMENGHO study were stratified according to the median of the plasma CML level (200.8 ng/ml; 25th percentile: 181.6 ng/ml, 75th percentile: 226.1 ng/ml) into "high CML" versus "low CML" as determined by ELISA. Local carotid artery properties, carotid intima media thickness (IMT), aortic pulse wave velocity (PWV), blood pressure and fetuin-A were analyzed. In 26 patients after carotidectomy, CML was visualized using immunohistochemistry. According to the CML median, groups were similar for anthropometric and biochemical data. Carotid diameter was enlarged in the "high" CML group (485.7+/-122.2 versus 421.2+/-133.2 microm; P<0.05), in particular in participants with elevated blood pressure and with "high" CML ("low" CML: 377.9+/-122.2 microm and "high" CML: 514.5+/-151.6 microm; P<0.001). CML was associated fetuin-A as marker of vascular inflammation in the whole cohort (r=0.28; P<0.01) and with carotid diameter in hypertensive subjects (r=0.42; P<0.01). CML level had no effect on aortic stiffness. CML was detected in the subendothelial space of human carotid arteries. In normoglycemic subjects CML was associated with carotid diameter without adaptive changes of elastic properties and with fetuin-A as vascular inflammation marker, in particular in subjects with elevated blood pressure. This may suggest qualitative changes of elastic fibers resulting in a defective mechanotransduction, in particular as CML is present in human carotid arteries.